Analisis Faktor-Faktor Penyebab Kesulitan Belajar Siswa Pada Pelajaran Kimia Materi Senyawa Hidrokarbon di MA Plus Nurul Islam Sekarbela - Zilatul Ariani; Dedi Riyan Rizaldi; Muhammad Fahrurrozi; Baiq Dewi Ratnasari; Nilwan; Ziadatul Fatimah (Lembaga Einstein College (LEC), 2024)
Indonesia is a country that has an education system that requires all its citizens to undergo 12 years of education. One of the levels of education is the senior high school level, which must be completed before entering college. At this level, chemistry is a compulsory subject for students majoring in science/mathematics. The purpose of this study was to analyze the factors causing students' learning difficulties in chemistry lessons on hydrocarbon compounds at MA Plus Nurul Islam Sekarbela. The method used in the study was a descriptive method with a qualitative approach. The descriptive method is intended to describe an object systematically and factually in terms of the nature and relationship between the symptoms studied or observed. Based on the results and discussions obtained, the factors causing students' learning difficulties in understanding hydrocarbon compounds are learning time, low interest and motivation in learning chemistry, weak ability to understand chemistry learning, and self-factors